2019
DOI: 10.3390/cells8060620
|View full text |Cite
|
Sign up to set email alerts
|

To See or Not to See: A Systematic Review of the Importance of Human Ocular Surface Cytokine Biosignatures in Ocular Allergy

Abstract: Cytokines are key cell signalling proteins in a number of immune and homeostatic pathways of the human body. In particular, they mediate intracellular mechanisms of allergy on the ocular surface by triggering cellular responses that result in typical physiological ocular allergy symptoms, such as itchiness, watery eyes, irritation, and swelling. Given the recent research focus in optometry on the aetiology of corneal ectasia subtypes like keratoconus, there is an increasing need for the development of new clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 70 publications
2
7
0
1
Order By: Relevance
“…Acute (seasonal allergic conjunctivitis) and iatrogenic (giant papillary conjunctivitis) forms of conjunctivitis demonstrated a lack of cytokine changes in the tears, while chronic diseases including vernal keratoconjunctivitis (VKC) and atopic keratoconjunctivitis (AKC) produced T helper (Th)1, Th2 cytokines and chemokines. [20][21][22] As observed in atopic dogs in this pilot study, IL-8 concentrations were found to be increased in the conjunctival epithelium of VKC and AKC in humans. IL-8 concentrations were correlated with disease severity as well as with the numbers of neutrophils and eosinophils.…”
Section: Discussionsupporting
confidence: 72%
“…Acute (seasonal allergic conjunctivitis) and iatrogenic (giant papillary conjunctivitis) forms of conjunctivitis demonstrated a lack of cytokine changes in the tears, while chronic diseases including vernal keratoconjunctivitis (VKC) and atopic keratoconjunctivitis (AKC) produced T helper (Th)1, Th2 cytokines and chemokines. [20][21][22] As observed in atopic dogs in this pilot study, IL-8 concentrations were found to be increased in the conjunctival epithelium of VKC and AKC in humans. IL-8 concentrations were correlated with disease severity as well as with the numbers of neutrophils and eosinophils.…”
Section: Discussionsupporting
confidence: 72%
“…The diagnosis of ocular allergies is primarily clinical, although laboratory tests can be useful in supporting the diagnosis 6 . At present, laboratory tests for AC mainly include cytological examination, skin prick tests, and total IgE antibody detection 15–17 . The detection of eosinophils is a complex procedure with a low detection rate of approximately 60% in conjunctival scrapings from patients with mild allergic conditions 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Allergic conjunctivitis (AC) is a common ocular surface disease that affects more than 20% of the population (1). It is well established in the literature that AC is closely related to the occurrence of keratoconus (KC) (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%